STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN NILAI SEMESTER SISWA UNTUK MENCAPAI ANGKA KRITERIA KETUNTASAN MINIMAL - Warjin Hi Soleman (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2017)
This study aims to find out the principal’s strategy in increasing the students’ semester score to reach the minimum criterion criteria. This research uses descriptive qualitative approach. Research location in SMP Negeri 14 West Halamahera North Maluku Province. The results showed that the principal’s strategy in increasing the students’ semester score to meet the minimum criteria, is: (1) the fulfillment of school infrastructure; (2) giving direction to teachers and learners with class visits; And (3) increased teacher professionalism. DOI: https://doi.org/10.17977/um025v1i32017p236